Islamic Educational Leadership In Prophetic Perspective - Syaikhul Kubro (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Leadership plays a crucial role in running an institution, be it an educational institution, social organization, or government agency. An effective leader is not only able to direct the vision and mission of the institution, but can also inspire and motivate team members to work together to achieve common goals. The inability of a leader to carry out his duties can have fatal consequences, which at one time can determine the success or failure of the institution as a whole. Therefore, an effective, fast, and responsive leader is needed to maximize the performance of an institution. Understanding Islamic educational leadership from a prophetic perspective is urgent in the midst of these challenges. Emulating the Prophet Muhammad SAW allows us to explore holistic and sustainable solutions. The prophetic perspective provides a strong moral foundation and a leadership model that has proven effective in overcoming human problems. Therefore, this study has practical relevance in answering the challenges of contemporary Islamic education. This paper will discuss the characteristics of prophetic leadership, with the hope of providing better insight into leading educational institutions today.